The role of Health Impact Assessment in the setting of air quality standards: an Australian perspective - Spickett, Jeffery; Katscherian, Dianne; Harris, P. (Elsevier Inc., 2013)
The approaches used for setting or reviewing air quality standards vary from country to country. The purpose of this research was to consider the potential to improve decision-making through integration of HIA into the processes to review and set air quality standards used in Australia. To assess the value of HIA in this policy process, its strengths and weaknesses were evaluated aligned with review of international processes for setting air quality standards. Air quality standard setting programmes elsewhere have either used HIA or have amalgamated and incorporated factors normally found within HIA frameworks. They clearly demonstrate the value of a formalised HIA process for setting air quality standards in Australia. The following elements should be taken into consideration when using HIA in standard setting. (a) The adequacy of a mainly technical approach in current standard setting procedures to consider social determinants of health. (b) The importance of risk assessment criteria and information within the HIA process. The assessment of risk should consider equity, the distribution of variations in air quality in different locations and the potential impacts on health. (c) The uncertainties in extrapolating evidence from one population to another or to subpopulations, especially the more vulnerable, due to differing environmental factors and population variables. (d) The significance of communication with all potential stakeholders on issues associated with the management of air quality. In Australia there is also an opportunity for HIA to be used in conjunction with the NEPM to develop local air quality standard measures. The outcomes of this research indicated that the use of HIA for air quality standard setting at the national and local levels would prove advantageous.